PENGEMBANGAN MEDIA APLIKASI CAPCUT BERBASIS KEARIFAN LOKAL PADA MATERI INDONESIAKU KAYA BUDAYA SISWA KELAS IV SD NEGERI 106843 JAHARUN B - Deswita Sirait; Tiflatul Husna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is an important aspect in human life. The progress of a country is influenced by education. Quality education determines the creation of a superior product or human being who can compete in the era of globalization. The researcher developed a CapCut Application Media with the Application producing an Animated learning Video that discusses the material My Indonesia is Rich in Culture in Class IV. The video would help teachers explain the material to class IV students more easily. According to the results of observations that had been carried out at SD Negeri 106843 Jaharun B, the results showed that learning media were very minimal because in the lower classes they only relied on textbooks. Likewise in the upper classes, teachers only provided learning through PPT and other printed books. When viewed, the printed books did not provide complete material containing examples from the area where the students currently live. Development research became the research design in this study. The process involves the Research and Development (R&D) cycle, which consists of the steps of studying research findings, field tests, and revisions.